Հովհաննես Երզնկացին (XIII դ.) լուսնի երկու տիպի ամիսների մասին - Էյնաթյան, Ջուլիետտա
Hovhannes Yerznkats‘i Pluz, an outstanding author of the 13thcentury, is known as poet, scholar, public and political figure. His literary heritage is in general studied but his cosmographic work still remains unexplored. In this article, we analyze his work entitled On the Celestial Movements, which is a written version of his extensive cosmographic sermon delivered in 1284 in the Cathedral of Tiflis. Of various topics discussed in this work, we have focused on focuses on the information about synodic and sidereal lunar months. Their difference is that in one case we deal with the movement of the Moon with respect to the moving Sun, and in the other, with respect to the stars. Unlike other thinkers who presented only the synodic month and followed the sequence of the phases of the Moon (since the day of Easter was determined according to the exact calculation of the synodic month), Hovhannes Yerznkats‘i also speaks about the sidereal month which had no relation to the feast calculations. Выдающийся автор XIII века Ованнес Ерзнкаци Плуз известен как поэт, ученый, общественный и политический деятель. Его труды в целом изучены, однако его космографическое сочинение до сих пор остаëтся неисследованным.Речь идëт о труде “О небесных движениях”, записанном варианте его пространной космографической речи, прочитанной в 1284 г. в кафедральном соборе Тифлиса. В данной статье из различных вопросов, обсуждаемых в речи, мы выделили сведения о синодических и сидерических месяцах Луны. Их разница состоит в том, что в одном случае мы имеем дело с движением Луны по отношению к движущемуся Солнцу, а в другом – по отношению к звëздам. В отличие от других мыслителей, которые представляли только синодический месяц и следили за последовательностью фаз Луны (так как по точному расчëту синодического месяца определялся день Пасхи), Ованнес Ерзнкаци говорит также о существовании сидерического месяца, который не имел отношения к праздничным расчëтам.
Keywords: Գրականություն; Աստղագիտություն